Utilizing Music Learning as Emotional Intelligence Therapy for Students with Intellectual Disabilities in Special Elementary Schools - Sularso, Sularso; Putri, Dheria Febriana; Hanshi, Bao (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2024)
This research is motivated by the fact that students with disabilities often have limitations in their cognitive abilities, making it challenging for them to comprehend learning materials delivered by teachers. The purpose of this study was to investigate the use of music learning as therapy to enhance emotional intelligence in students with disabilities. This qualitative descriptive research utilized data collection techniques including observation, interviews, and documentation. Data analysis involved data collection, data reduction, data presentation, and conclusion. Data validity was ensured through source triangulation and technique triangulation. The research subjects included music teachers, classroom teachers, and five students with disabilities. The results revealed that singing was the primary form of music learning taught to students with disabilities at SDLB N 1 Yogyakarta. This approach had a positive impact on the emotional intelligence of these students, enabling them to better control their emotions during the learning process. Students with disabilities demonstrated improvements in various components of emotional intelligence. The study identified supportive factors such as facilities, infrastructure, and learning components, as well as inhibiting factors related to students' conditions during the learning process. This research contributes to the understanding of music learning as a form of emotional intelligence therapy for students with disabilities.